Effectiveness of Using Pocket Book Learning Media in History Subjects For Grade XI IPS Student at MAN 1 South Aceh - Wulandari*, Liska; Sakdiyah, Sakdiyah; Kesuma, T. Bahagia (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
Study This discuss about effectiveness use of pocket book learning media on the eyes lesson history student class XI IPS MAN 1 South Aceh. Lack of source learning available at school make student must take notes summary material learn and just based on notes the result in low results learning obtained by students. Research This aiming For know results Study student with using pocket book media, and response student after Study using pocket book media. research This use approach quantitative. As for what becomes subject study This is student class XI IPS consisting of 21 students with use instrument collection of test and questionnaire data. Test results student show mark completeness classical student reached 76% which includes in good category, average class value after use pocket book media reached 74.52 ( good ), while the average value student before using pocket book media is 62. The percentage result response student to use of pocket book media in the eyes lesson history is 79% ( good ). With thus can known How effectiveness use of Pocket Book media in the eyes lesson history.